A dual-modal ROS generator based on multifunctional PDA–MnO2@Ce6 nanozymes for synergistic chemo-photodynamic antibacterial therapy. (8th February 2023) - Cui, Anni; Bao, Ying; Xu, Haitao; Mu, Xin; Zhong, Xiahua; Wee, Wynn; Wu, Fanqi; Shan, Guiye
Abstract : PMCL nanozymes catalyze endogenous H2 O2  to achieve O2  self-supplied PDT and improve the OH generation by photothermal effect. Based on dual-enzyme activities, PMCL exhibits powerful antibacterial efficacy and mature bacterial biofilm eradication. Abstract : The rapid emergence of drug-resistant bacteria has attracted great attention to exploring advanced antibacterial methods. However, single-modal antibacterial therapy cannot easily eliminate drug-resistant bacteria completely due to its low efficacy. Therefore, it is essential to achieve multi-modal antibacterial therapy effectively. Herein, a dual-modal ROS generator was designed based on photosensitive PDA–MnO2 @Ce6/liposome (PMCL) nanozymes for synergistic chemo-photodynamic therapy. PMCL nanozymes adhere to bacteria through liposome–membrane fusion. Meanwhile, PMCL catalyzes endogenous hydrogen peroxide (H2 O2 ) to generate hydroxyl radicals (˙OH) and singlet oxygen ( 1 O2 ) under laser irradiation. Furthermore, the photothermal effect can accelerate the generation of ROS. Based on dual-enzyme activities (mimicking peroxidase and catalase) and photodynamic properties, PMCL achieves powerful antibacterial efficacy and mature bacterial biofilm eradication. With the synergistic chemo-photodynamic effects, bacterial populations decrease by >99.76% against Gram-positive S. aureus and Gram-negative E. coli . Notably, the synergistic antibacterial properties of PMCL nanozymes are further explored using a mouse wound model of S. aureus infection. This work fabricated an efficient dual-modal ROS generator to kill bacteria, further providing a new strategy for treating wound infection.